Z-scan fluorescence correlation spectroscopy as a tool for diffusion measurements in planar lipid membranes - Steinberger, Tomáš; Macháň, Radek; Hof, Martin (Methods in molecular biology (Clifton, N.J.), 2014)
Studies of lateral diffusion are used for the characterization of the dynamics of biological membranes. One of the techniques that can be used for this purpose is fluorescence correlation spectroscopy (FCS), which belongs to the single-molecule techniques. Unfortunately, FCS measurements, when performed in planar lipid systems, are associated with a few sources of inaccuracy in the determination of the lateral diffusion coefficient. The main problems are related to the imperfect positioning of the laser focus relative to the plane of the sample. Another source of inaccuracy is the requirement for external calibration of the detection volume size. This protocol introduces a calibration-free method called Z-scan fluorescence correlation spectroscopy (Z-scan FCS), which is based on the determination of the diffusion time and particle number in steps along the optical (z-) axis by sequential FCS measurements. Z-scan FCS could be employed for diffusion measurements in planar membrane model systems-supported phospholipid bilayers (SPBs) and giant unilamellar vesicles (GUVs) and also in biological membranes. A result from measurements in SPBs is also presented in the protocol as a principle example of the Z-scan technique.
Keywords: Membrane Lipids; Fluorescence; Lipid Bilayers; Membrane Fluidity; teoretické modely; Cell Membrane; lipidové dvojvrstvy; Diffusion; Models, Theoretical; difuze; Spectrometry, Fluorescence; membránové lipidy; fluorescenční spektrometrie; Calibration; fluidita membrány; fluorescence; kalibrace; buněčná membrána